UPLC-MS/MS Technology for the Quantitative Methodology and Pharmacokinetic Analysis of Voxtalisib in Rat Plasma - Li, Qingqing; Liu, Ya-nan; Wang, Jing; Hu, Yingying; Hu, Jinyu; Xu, Ren-ai; Shao, Liu; Chen, Lianguo (Frontiers in Pharmacology, 2022)
Voxtalisib, is a specific, effective, and reversible dual inhibitor, which inhibits both Class I P13K and mTOR. To date, voxtalisib has been studied in trials for melanoma, lymphoma, glioblastoma, breast cancer, and other cancers. In this study, a highly sensitive and rapid ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) technology was applied for the quantitative methodology and pharmacokinetic analysis of voxtalisib in rat plasma. After protein precipitation of the analyte by acetonitrile, the chromatographic separation was performed by gradient elution on an Acquity BEH C18 column (2.1 mm × 50 mm, 1.7μm) with acetonitrile (solvent A) and 0.1% formic acid (solvent B) as the mobile phase. Selective reaction monitoring (SRM) in positive ion mode, the mass transfer detection of the analyte and IS was m/z 270.91>242.98 and m/z 572.30>246.10, respectively. In the concentration range of 1-2000ng/ mL, a good linear relationship was successfully established by the UPLC-MS/MS technology, and the lower limit of quantification (LLOQ) was determined as 1ng/mL. Intra-day and inter-day precision for voxtalisib were 7.5% to 10.6% and 13.0% to 14.3%, respectively, and the accuracies were in the ranges of -4.0% to -14.0% and 4.4% to 7.2%, respectively. The matrix effect, extraction recovery, and stability of the analyte were all in compliance with the acceptance criteria of bioassays recommended by FDA. Finally, the pharmacokinetic profile of the analyte could be availably studied by the UPLC-MS/MS bio-analytical method after the rats were treated by intragastric administration with voxtalisib (5 mg/kg).